Hubungan Dukungan Sosial Orang Tua dengan Hasil Belajar Santri di MDA Nurul Haq Nagari Cubadak Kecamatan Dua Koto Kabupaten Pasaman - Marina Siska; Solfema Solfema; Wirdaul Aini (Universitas Negeri Padang, 2018)
The research motivated by the low of study result of santri, which is suspected because of the low of parent support received by santri at MDA Nurul Haq Nagari Cubadak Kecamatan Dua Koto Kabupaten Pasaman. This study aims to (1) describe the support of parents, (2) describe the students' learning outcomes, and (3) to see the relationship of parent support with students learning outcomes. The type from research is quantitative correlational. Population in as many as 40 people santri. The sampling technique used stratified random sampling. Samples taken as much as 50% ie 20 people. Data collection techniques are questionnaires, while data analysis uses the percentage formula and Saperman Rho. The results of the study found that (1) Parental support is categorized as low. (2) Students' learning outcomes in categorized are still low. (3) There is a significant relationship between parental support and student learning outcomes at. Suggested (1) To parents, to further improve the provision of support to children (2) To the students are expected to be more active in learning so that the results obtained high learning (3) To the next researcher, in order to see other factors that have not been studied in research this.